Electron flow of biological H2 production by sludge under simple thermal treatment: Kinetic study - Amin, Mohammad Mehdi; Taheri, Ensiyeh; Bina, Bijan; van Ginkel, Steven W.; Ghasemian, Mohammad; Mohamad Puad, Noor Illi; Fatehizadeh, Ali (Elsevier Inc., 2019)
Mixed culture sludge has been widely used as a microbial consortium for biohydrogen production. Simple thermal treatment of sludge is usually required in order to eliminate any H2-consuming bacteria that would reduce H2 production. In this study, thermal treatment of sludge was carried out at various temperatures. Electron flow model was then applied in order to assess community structure in the sludge upon thermal treatment for biohydrogen production. Results show that the dominant electron sink was acetate (150–217 eˉ meq/mol glucose). The electron equivalent (eˉ eq) balances were within 0.8–18% for all experiments. Treatment at 100 °C attained the highest H2 yield of 3.44 mol H2/mol glucose from the stoichiometric reaction. As the treatment temperature increased from 80 to 100 °C, the computed acetyl-CoA and reduced form of ferredoxin (Fdred) concentrations increased from 13.01 to 17.34 eˉ eq (1.63–2.17 mol) and 1.34 to 4.18 eˉ eq (0.67–2.09 mol), respectively. The NADH2 balance error varied from 3 to 10% and the term eˉ(Fd↔NADH2) (m) in the NADH2 balance was NADH2 consumption (m = −1). The H2 production was mainly via the Fd:hydrogenase system and this is supported with a good NADH2 balance. Using the modified Gompertz model, the highest maximum H2 production potential was 1194 mL whereas the maximum rate of H2 production was 357 mL/h recorded at 100 °C of treatment.